我国油橄榄产业发展的挑战与对策Challenges and countermeasures in the development of olive industry in China - 龙伟1，曾燕如2，盛建喜3 LONG Wei1, ZENG Yanru2, SHENG Jianxi3 (Zhongguo youzhi, 2023)
油橄榄具有速生、高产和果实含油率高等优点，在食品营养、医药健康和景观绿化中有着广泛的应用。为明晰我国油橄榄产业发展现状、问题和发展方向，分析了油橄榄种质资源及我国油橄榄种植与发展的现状，剖析了我国油橄榄产业面临的种质资源混杂、选育落后，品种特性认识不足，产品开发有待提高等挑战，并提出应对挑战的对策，以期为我国油橄榄产业科学发展提供参考。Olive has the advantages of rapid growth, high yield, and high oil content,and it is widely applied in food nutrition, medical health, and landscape greening. Aiming to clarify the development status, problems, and development direction of China′s olive industry, the olive germplasm resources, planting and development status of China were analyzed.The challenges faced by the olive industry in China, such as mixed germplasm resources, backward breeding and insufficient understanding of variety characteristis and the need to improve product development were analyzed, and countermeasures to deal with the challenges were put forward, in order to provide reference for the scientific development of China′s olive industry.